MAKNA TRADISI MALAM BAINAI DALAM PERNIKAHAN ADAT MINANGKABAU DI DESA PADANG LAWEH KECAMATAN SUNGAI TARAB KOTA BATUSANGKAR - Dwi Maharani; Aulia Fitri (Jurnal Komunikasi dan Budaya, 2022)
Indonesia is a country that has a diversity of ethnic groups that have different customs and cultures. From various cultures, each has its own traditions and customs, one of which is the tradition of the Minangkabau, there is a culture, namely a tradition called Malam Bainai. The night of Bainai is to redden the bride's nails with crushed henna leaves. The Bainai night event is held at Anak Daro's house, which is held on the night of the day before the wedding day. The formulation of the problem in this study is "What is the meaning of the Bainai night in a Minangkabau traditional wedding in Padang Laweh Village, Sungai Tarab District, Batusangkar City?". The aim of this research is to find out the implementation of the Bainai night at the Minangkabau traditional wedding. This study uses a descriptive method, with data collection techniques using interviews, observation, documentation and analyzing data with qualitative techniques.